2022
DOI: 10.1093/g3journal/jkac131
|View full text |Cite
|
Sign up to set email alerts
|

Spodoptera littoralis genome mining brings insights on the dynamic of expansion of gustatory receptors in polyphagous noctuidae

Abstract: The bitter taste, triggered via gustatory receptors, serves as an important natural defense against the ingestion of poisonous foods in animals, and the increased host breadth is usually linked to an increase in the number of gustatory receptor genes. This has been especially observed in polyphagous insect species, such as noctuid species from the Spodoptera genus. However, the dynamic and physical mechanisms leading to these gene expansions and the evolutionary pressures behind them remain elusive. Among majo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 89 publications
(125 reference statements)
0
12
0
Order By: Relevance
“…littoralis expansion of its host range by increasing the number of gustatory receptor copies (Meslin et al, 2022). Our study found that both M. separata and M. loreyi have increased copies of α-amylase, and we hypothesize that transposon expansion and insertion may contribute to their adaptation by enhancing energy metabolism and promoting long-distance migration (Figure 5, Figure S8).…”
Section: Discussionmentioning
confidence: 66%
“…littoralis expansion of its host range by increasing the number of gustatory receptor copies (Meslin et al, 2022). Our study found that both M. separata and M. loreyi have increased copies of α-amylase, and we hypothesize that transposon expansion and insertion may contribute to their adaptation by enhancing energy metabolism and promoting long-distance migration (Figure 5, Figure S8).…”
Section: Discussionmentioning
confidence: 66%
“…The first insect Grs were identified in Drosophila melanogaster [15,16]. Additional Gr data are limited to published genome sequences of particular species including Bombyx mori [17][18][19], Heliconius melpomene [20], Plutella xylostella [21][22][23] and Manduca sexta [24]. Insect Grs often possess seven transmembrane domains with reverse topology when compared with classical G-protein coupled receptors, with an intracellular N-terminus and an extracellular C-terminus [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…This high number of genes compared with other Nymphalidae (including D. plexippus ) results from extensive duplications in Ithomiini that occurred in several lineages of the GR phylogeny (Figure 4). So far, such expansions of GR repertoires in Lepidoptera have been documented only in the Noctuidae family, where it has been tentatively linked to polyphagy (Gouin et al, 2017; Meslin et al, 2022). It is interesting to note that somehow similar expansions also occurred independently in Ithomiini, which are not polyphagous but rather oligophagous species (McClure & Elias, 2016b; Willmott & Mallet, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…For each of the chemosensory gene family, that is, odorant receptors (ORs), the gustatory receptors (GRs), the variant ionotropic receptors (IRs), the odorant‐binding proteins (OBPs) and the chemosensory proteins (CSPs), amino acid sequences previously identified from the genomes of D. plexippus , H. melpomene , S. frugiperda and B. mori (Briscoe et al, 2013; Gouin et al, 2017; Guo et al, 2017; Heliconius Genome Consortium, 2012; Liu et al, 2018; Meslin et al, 2022; Vogt et al, 2015; Zhan et al, 2011) as well as from the transcriptome of M. marsaeus (Piron‐Prunier et al, 2021) were used as queries in a tBLASTn search against genome assemblies of the three species (e‐value threshold 0.001), in order to identify scaffolds containing the genes to annotate. Query amino acid sequences were then aligned on these scaffolds with Exonerate (Slater & Birney, 2005) to identify precise intron‐exon boundaries and create gene models.…”
Section: Methodsmentioning
confidence: 99%